Eccentric-weave FSW between Cu and AA 6061-T6 with reinforced Graphene nanoparticles. Issue 3 (17th February 2018) - Jayabalakrishnan, D.; Balasubramanian, M.
ABSTRACT: This study deals with the retrofication of micro- and macrostructural defects in joining aluminum and copper alloy using eccentric weave friction stir welding. In addition, graphene nanoparticles were added to strengthen the weldments. Welding experiments were conducted with two types of stir tool as (normal and offset pin) in linear and eccentric weave pattern. Results from this study reveal the possibility of tool tribology on eccentric stirring with tool pin offset producing a very minimal wear of 5 µm in comparison to other patterns of weld; defects on microscopic and macroscopic view of the weldments prove the existence of fragmental cracks in eccentric welding, and mechanical properties viz. yield strength of 187 MPa, ultimate tensile strength of 217 MPa, and elongation of 10% were found for the eccentric weave welded joints. This reveals the achievement of robust welded joints in the aluminum and copper alloys by eccentric weave welding with pin offset.